2016
DOI: 10.1016/j.ijrobp.2015.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Improving Tumor Treating Fields Treatment Efficacy in Patients With Glioblastoma Using Personalized Array Layouts

Abstract: These results suggest that adapting array layouts to specific tumor locations can significantly increase field strength within the tumor. Our findings support the idea of personalized treatment planning to increase TTFields efficacy for patients with GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 20 publications
3
61
1
Order By: Relevance
“…In accordance to the data present by Wenger et al. , we also noted changes in TTFields at the GTV depending on array positioning, with significant variability in the electric field strength of GTV between 100 and 150 V/m, ranging from only 20% volume having 100 V/m with clockwise rotation of the lateral arrays and no displacement of the anterior–posterior arrays to >40% volume having at least 150 V/m when the lateral arrays are rotated in a counterclockwise fashion and the anterior array is moved backward. SAR variability in the rate of energy deposition was less dramatic, as the magnitude of SAR 50% changes between 3 and 6 W/kg.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance to the data present by Wenger et al. , we also noted changes in TTFields at the GTV depending on array positioning, with significant variability in the electric field strength of GTV between 100 and 150 V/m, ranging from only 20% volume having 100 V/m with clockwise rotation of the lateral arrays and no displacement of the anterior–posterior arrays to >40% volume having at least 150 V/m when the lateral arrays are rotated in a counterclockwise fashion and the anterior array is moved backward. SAR variability in the rate of energy deposition was less dramatic, as the magnitude of SAR 50% changes between 3 and 6 W/kg.…”
Section: Discussionsupporting
confidence: 92%
“…TTFields are applied to the shaved scalp via two pairs of orthogonally positioned transducer arrays. Clinical placement of the arrays is determined by the proprietary NovoTAL TM software that generates an array layout diagram . Each array has nine ceramic disks acting like disk sources for the electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…Spherical tumor lesions were subsequently introduced by post-processing of the mesh. All lesions had external diameters of 20 mm and inner core diameters of 14 mm, corresponding tumor sizes as previously investigated by Miranda et al [2729]. For each location of the tumor, two scenarios were investigated: 1) Tumor with central necrosis, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In order to estimate field intensity distributions within the lesions, numerical simulations were performed using finite element method calculations and a realistic head model created as previously described (9,10). Briefly, tumor tissues were segmented manually using a T1 contrast MRI of the patient.…”
Section: Calculation Of Ttfields Intensitymentioning
confidence: 99%
“…Tumor-treating fields therapy was used together with maintenance TMZ for six TMZ cycles and was continued as a monotherapy for additional 14 months. The placement of the transducer arrays, through which TTFields are applied, was calculated using the NovoTAL TM methodology (9,10). Despite the deep location of the lesion, numeric simulations (Figure 4) demonstrated that the field intensity delivered to the lesion was above therapeutic levels (>1 V/cm).…”
Section: Ttfieldsmentioning
confidence: 99%